2022
DOI: 10.3389/fcell.2022.826053
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Chemokines at the Maternal–Fetal Interface

Abstract: Successful pregnancy requires the maternal immune system to tolerate the semi-allogeneic embryo. A good trophoblast function is also essential for successful embryo implantation and subsequent placental development. Chemokines are initially described in recruiting leukocytes. There are rich chemokines and chemokine receptor system at the maternal–fetal interface. Numerous studies have reported that they not only regulate trophoblast biological behaviors but also participate in the decidual immune response. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 133 publications
0
20
0
Order By: Relevance
“…Currently, it was wellaccepted that there are abundant chemokines and chemokine receptor systems at the maternal-fetal interface. 19,27 During the remodeling process of maternal arteries, EVT invades decidua and elicits allogeneic immune responses by maternal T and NK cells, which then contribute to maternal-fetal immune tolerance. 28 These soluble factors were also reported to not only regulate EVT invasion but also contribute to the decidual immune response via chemokine receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, it was wellaccepted that there are abundant chemokines and chemokine receptor systems at the maternal-fetal interface. 19,27 During the remodeling process of maternal arteries, EVT invades decidua and elicits allogeneic immune responses by maternal T and NK cells, which then contribute to maternal-fetal immune tolerance. 28 These soluble factors were also reported to not only regulate EVT invasion but also contribute to the decidual immune response via chemokine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that Swan71 cells induce the expression of various chemokines in the spheroid culture. Currently, it was well‐accepted that there are abundant chemokines and chemokine receptor systems at the maternal‐fetal interface 19,27 . During the remodeling process of maternal arteries, EVT invades decidua and elicits allogeneic immune responses by maternal T and NK cells, which then contribute to maternal‐fetal immune tolerance 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines and chemokines play an important role in embryogenesis through the mediation of cell survival, proliferation, differentiation, and promotion of cell adhesion to specific sites to coordinate invasion of fetal trophoblasts into the maternal decidua [18][19][20][21]. Dysregulation in the establishment of a healthy placenta can result in maternal and fetal pathologies such as preeclampsia, spontaneous pre-term birth, intra-uterine growth restrictions, and resorption [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%